Budidaya Ikan Lele untuk Menunjang Kelancaran Biaya Operasional TPQ dan RTQ Raudhatul Adzkia Jorong Dalam Koto Kabupaten Agam - Refilda Refilda; Rahmiana Zein; Yefrida Yefrida; Zilfa Zilfa; Upita Septiani; Syukri Syukri; Diana Vanda Wellia; Syafrizayanti Syafrizayanti; Matlal Fajri Alif; Elida Mardiah; Refinel Refinel; Admi Admi; Emil Salim; Fitratul Ilahi; Dwi Syukur Phameswari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
The Qur'an Education Park (TPQ) and Tahzhul Qur'an House (RTQ) of the Raudhatul Adzkia Jorong Dalam Koto Nagari Koto Tangah, Tilatang Kamang, and District of Agam have been launched since 2015. The students who study here are free of charge. The operational costs of education and the honorarium for educators come from donations from their community and some nomads. However, this contribution is not sufficient for operational costs. The Department of Chemistry's community service team, Andalas University, collaborated with partners to start a business to solve this problem. The business was carried out using vacant land owned by partners for catfish cultivation. Surveys, program socialization and assisting activities were carried out online using virtual media, while Partners carried out the implementation in the field. Activities carried out were pond preparation, the release of catfish seeds, feeding, sorting, maintenance, harvesting, and marketing cultivated catfish. Based on the evaluation, 5000 seedlings from the released catfish developed well. About 99% of catfish typically growth to a large and even size, while the other 1% growth relatively slowly. Harvested catfish were sold for IDR 18,000/kg for wet fish and IDR 100,000/kg for dried fish. This business has been carried out sustainably by partners, and the profits have been used to support the operational costs of TPQ and RTQ Raudhatul Adzkia.